Protein protein interations in estrogen receptor biology Involvement of a nuclear localization sequence binding protein and ubiquitin - (:unkn) unknown (Hyderabad, 2014)
None
_
Keywords: Protein; Estrogen; Interations; Receptor; Involvement; Localization